2010
DOI: 10.3109/09638281003611078
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in stroke functional outcomes upon discharge from inpatient rehabilitation facilities

Abstract: Controlling for patient characteristics, therapy intensity and processes of care results in non-significant differences between African-Americans and whites in motor FIM scores upon discharge. The absence of significant differences in recovery while patients were on the rehabilitation unit suggests that racial disparities in long-term functional recovery after stroke are likely to have originated before or after the inpatient rehabilitation stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…In direct contrast, Berges et al noted significant differences at 3 months post injury while finding no significant differences at discharge [7]. When examining change over time, another study observed that whites demonstrated greater overall gains in FIM total and cognitive scores from admission to discharge [8], although once admission FIM scores were statistically accounted for, these significant racial/ethnic differences in post-acute rehabilitation outcomes were eliminated [9][10][11][12].…”
Section: Differences In Rehabilitation Outcomementioning
confidence: 77%
“…In direct contrast, Berges et al noted significant differences at 3 months post injury while finding no significant differences at discharge [7]. When examining change over time, another study observed that whites demonstrated greater overall gains in FIM total and cognitive scores from admission to discharge [8], although once admission FIM scores were statistically accounted for, these significant racial/ethnic differences in post-acute rehabilitation outcomes were eliminated [9][10][11][12].…”
Section: Differences In Rehabilitation Outcomementioning
confidence: 77%
“…Ten of the 17 studies reported statistically significant racial/ethnic differences in poststroke rehabilitation outcomes [11, 1720, 22, 23, 27, 28, 31]. The most widely reported outcome measure was the functional independence measure (FIM) [32].…”
Section: Resultsmentioning
confidence: 99%
“…Early rehabilitation occurs in a specialized stroke unit [12,7]. Rehabilitation involves services that endeavor to decrease impairment while enhancing restoration and adaptation to residue disabilities [13]. As asserted by Putaman [13], rehabilitation is a continuous course that includes identification of challenges and needs.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation involves services that endeavor to decrease impairment while enhancing restoration and adaptation to residue disabilities [13]. As asserted by Putaman [13], rehabilitation is a continuous course that includes identification of challenges and needs. Significantly, the authors indicated that International Classification of Functions (ICF) can be utilized to supervise rehabilitation from hospital to community reintegration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation